Tumor alkalization therapy: misconception or good therapeutics perspective? – the case of malignant ascites - Bogdanov, Alexey; Verlov, Nikolay; Bogdanov, Andrey; Burdakov, Vladimir; Semiletov, Valeriy; Egorenkov, Vitaliy; Volkov, Nikita; Moiseyenko, Vladimir (Frontiers in Oncology, 2024)
Tumor acidity has been identified as a key factor in promoting cancer progression, metastasis, and resistance. Tumor alkalization therapy has emerged as a potential strategy for cancer treatment. This article provides preclinical and clinical evidence for tumor alkalization therapy as a promising cancer treatment strategy. The potential of tumor alkalization therapy using sodium bicarbonate in the treatment of malignant ascites was studied. The concept of intraperitoneal perfusion with an alkalizing solution to increase the extracellular pH and its antitumor effect were explored. The significant extension in the overall survival of the Ehrlich ascites carcinoma mice treated with sodium bicarbonate solution compared to those treated with a sodium chloride solution was observed. In the sodium bicarbonate group, mice had a median survival of 30 days after tumor cell injection, which was significantly (p<0.05) different from the median survival of 18 days in the sodium chloride group and 14 days in the intact group. We also performed a case study of a patient with ovarian cancer malignant ascites resistant to previous lines of chemotherapy who underwent intraperitoneal perfusions with a sodium bicarbonate solution, resulting in a significant drop of CA-125 levels from 5600 U/mL to 2200 U/mL in and disappearance of ascites, indicating the potential effectiveness of the treatment. The preclinical and clinical results obtained using sodium bicarbonate perfusion in the treatment of malignant ascites represent a small yet significant contribution to the evolving field of tumor alkalization as a cancer therapy. They unequivocally affirm the good prospects of this concept.